Analysis on mechanism of explosive spalling resistance of aluminum powder on ladle corundum-based refractory castable. Issue 11 (1st August 2020) - Wang, Zhiqiang; Li, Xiangcheng; Zhu, Boquan; Lei, Zhongxing; Peng, Xiaoqian; Wang, Yulong
Abstract: The effect of the particle size (50–325 mesh) and content (0–0.1 wt%) of metallic aluminum powder on the explosive spalling resistance of corundum-based refractory castables were investigated in this study based on air permeability, pore size distribution, heat release, fracture energy and microstructural analyses. The experimental results show that the addition of Al powder significantly improves their explosive spalling resistance. As observed, the explosive spalling resistance of the castables was mainly influenced by the permeability mechanism and the fracture energy. Permeable paths were generated in the microstructure of the sample during the overlapping period between the curing process and the H2 gas forming one, derived from the Al–H2 O reaction. The highest permeability level was obtained when 0.075 wt % of Al powder with size of 100 mesh was incorporated into the corundum-based refractory castables. At the same time, the fracture energy of the castable samples was increased accordingly.